Topical brimonidine tartrate as a novel treatment for facial erythema of rosacea and acne erythema. Issue 2 (May 2016) - Genedy, Rasha M.
Abstract : Background: Facial erythema is often observed in almost all subtypes of rosacea and may complicate acne vulgaris. It presents a significant therapeutic challenge. There are many topical treatments available for rosacea and acne vulgaris, and yet none of them directly targets the erythematous component of these two diseases. Brimonidine, a highly selective α2 -adrenergic receptor agonist, can cause constriction of peripheral vasculature. Objective: To evaluate the efficacy and safety of topical brimonidine tartrate in the treatment of erythema of rosacea and postacne erythema. Patients and methods: For 30 patients with rosacea and 30 patients with postacne erythema, topical brimonidine tartrate 0.2% solution was applied twice daily for 4 weeks. Both groups were followed up for 4 weeks after stopping the treatment. Erythema was assessed every 2 weeks during the treatment phase and at the end of the follow-up phase. Results: Erythema score gradually decreased during the 4 weeks of treatment with brimonidine in both groups. This improvement was statistically significant at the end of the treatment phase. At the end of the follow-up period, erythema was still significantly lower than that at the time of enrollment in both groups. The improvement was significantly higher in the acne group than in the rosacea group at the end of both the treatment phase and the follow-up period. Conclusion: Topical brimonidine is considered both effective and safe in the treatment of postacne erythema as well as rosacea erythema. It could be considered as a therapeutic alternative to laser therapy for patients with the above-mentioned diseases.